STORYTELLING DEVELOPMENT MODEL USING CHAIN STORY TECHNIQUE IN EARLY CHILDHOOD - Nurzannah, Nurzannah; Sitepu, Juli Maini; Z, Zailani (Proceeding International Seminar of Islamic Studies, 2022)
The specific objective of this research is to develop a storytelling model using the chain story technique for early childhood. The research method used is document analysis, observation, and interviews. The results showed that the implementation of the storytelling method carried out by the ABA Aisyiyah Kindergarten teachers in Medan City was classified as good (it was listed in the RPPH), and had met the standards and criteria for implementing the storytelling method in early childhood. However, it is still teacher-centered. The storytelling development model using the Chain Story technique is packaged so that storytelling is not carried out solely by the teacher, but is carried out by students (student-centered). The teacher is only a trigger for stories with a short duration. While students tell stories freely, using their way and style. The teacher only supervises and controls the course of the stories carried out by the students so that they remain by the themes and learning objectives set in the RPPH while assessing when the students are telling stories.